The burden of illness of patients with paroxysmal nocturnal haemoglobinuria receiving C5 inhibitors: clinical outcomes and medical encounters from the patient perspective. Issue 1 (31st December 2022) - Sicre de Fontbrune, Flore; Burmester, Pascale; Piggin, Maria; Matos, Joana E.; Costantino, Halley; Wilson, Koo; Hakimi, Zalmai; Nazir, Jameel; Desgraz, Renaud; Fishman, Jesse; Persson, Emmelie; Panse, Jens
ABSTRACT: Objectives: To assess the clinical and healthcare resource burden among C5 inhibitor (C5i)-treated patients with paroxysmal nocturnal haemoglobinuria (PNH), using patient-reported data. Methods: This web-based, cross-sectional survey (01FEB2021–31MAR2021) of adults with PNH treated with eculizumab (France, Germany, UK) or ravulizumab (Germany) included: patient characteristics; treatment patterns/dosage; haematological outcomes (haemoglobin [Hb] levels, transfusions, thrombotic events, breakthrough haemolysis); and medical encounters. Treatment and Hb-level subgroup differences were assessed with statistical significance tests. Results: Among 71 patients, 98.6% were C5i-treated for ≥3 months. The majority (with reported Hb levels) had levels ≤12.0 g/dL (85.7%; n = 54/63). The mean Hb level was 10.2 g/dL (standard deviation [SD]: 2.0; median 10.0 g/dL). Treatment with above label-recommended doses was reported by 30.4% (eculizumab) and 5.3% (ravulizumab) of patients. Within the past 12 months among patients treated with C5i for ≥1 year: 24.1% had ≥1 transfusion; 3.2% had ≥1 thrombosis; and 28.6% had ≥1 breakthrough haemolysis. Among all patients, 26.8% and 31.0% reported emergency department/room [ER] and inpatient visits, respectively. Mean annual, per-patient all-cause medical encounters were: 0.5 (ER); 1.9 (inpatient); and overall outpatient visits ranged by setting from 2.0 to 6.4. Most encounters were PNH-related, with means of 0.4 (ER); 1.8 (inpatient); and 1.6–5.4 (outpatient). Primary haematological and medical encounter outcomes were similar between treatment as well as Hb-level subgroups, with almost no statistically significant differences. Conclusions: Despite at least 3 months of C5i treatment, high proportions of patients with PNH reported low haemoglobin levels and required transfusions and hospitalizations, which suggests remaining unmet needs.